J2EE™ Security for Servlets, EJBs and Web Services: Applying Theory and Standards to Practice - Kumar, Pankaj (Hewlett-Packard professional books., 2003)
J2EE developers have an extraordinary array of powerful options for securing their Web services, Web applications, EJB components and RMI objects. Now, expert Java architect Pankaj Kumar helps developers make sense of Java's increasingly rich security APIs, tools, patterns, and best practices-showing how to use each of them in the right place, at the right time, and in the right way. Kumar covers every significant J2SE and J2EE security mechanism, presenting practical implementation techniques for the entire J2EE project lifecycle: analysis, design, development, deployment and operations. The book's example-rich coverage includes: Implementing cryptography with the JCA (Java Cryptography Architecture) and JCE (Java Cryptography Extension) security APIs Building PKI systems with Java: implementing X.509 certificates, Certification Authorities, Certificate Revocation Lists, and repositories Java security managers, policy files, and JAAS: implementing access control based on code origin, code signer and user credentials Securing the wire: Using SSL and the JSSE API to secure data exchange over unprotected networks Ensuring XML message integrity, authentication, and confidentiality with the standards: XML Signature and XML Encryption using the VeriSign TSIK, and Infomosaic SecureXML libraries Addressing security issues in RMI-based distributed applications Developing and deploying servlets and EJBs for authenticated and secure access Securing Web services with transport- and message-based security: SSL for transport-based and WS Security for message-based security Covering security aspects of best-of-breed products: Apache Tomcat, Apache Axis, and BEA WebLogic Server.